Loss of Polycomb proteins CLF and LHP1 leads to excessive RNA degradation in Arabidopsis. (20th May 2022) - Séré, David; Cassan, Océane; Bellegarde, Fanny; Fizames, Cécile; Boucherez, Jossia; Schivre, Geoffrey; Azevedo, Jacinthe; Lagrange, Thierry; Gojon, Alain; Martin, Antoine
Abstract: Polycomb-group (PcG) proteins are major chromatin complexes that regulate gene expression, mainly described as repressors keeping genes in a transcriptionally silent state during development. Recent studies have nonetheless suggested that PcG proteins might have additional functions, including targeting active genes or acting independently of gene expression regulation. However, the reasons for the implication of PcG proteins and their associated chromatin marks on active genes are still largely unknown. Here, we report that combining mutations for CURLY LEAF (CLF) and LIKE HETEROCHROMATIN PROTEIN1 (LHP1), two Arabidopsis PcG proteins, results in deregulation of expression of active genes that are targeted by PcG proteins or enriched in associated chromatin marks. We show that this deregulation is associated with accumulation of small RNAs corresponding to massive degradation of active gene transcripts. We demonstrate that transcriptionally active genes and especially those targeted by PcG proteins are prone to RNA degradation, even though deregulation of RNA degradation following the loss of function of PcG proteins is not likely to be mediated by a PcG protein-mediated chromatin environment. Therefore, we conclude that PcG protein function is essential to maintain an accurate level of RNA degradation to ensure accurate gene expression. Abstract : The function of Polycomb-group proteins is essential to regulate the homeostasis of RNA degradation, and ensure suitable gene expression levels.